2020
DOI: 10.3390/act9030057
|View full text |Cite
|
Sign up to set email alerts
|

Recent Structure Development of Poly(vinylidene fluoride)-Based Piezoelectric Nanogenerator for Self-Powered Sensor

Abstract: As the internet of things (IoT) era approaches, various sensors, and wireless electronic devices such as smartphones, smart watches, and earphones are emerging. As the types and functions of electronics are diversified, the energy consumption of electronics increases, which causes battery charging and maintenance issues. The piezoelectric nanogenerator (PENG) received great attention as an alternative to solving the energy issues of future small electronics. In particular, polyvinylidene fluoride (PVDF) piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 118 publications
0
17
0
Order By: Relevance
“…In this paper, an encapsulation layer thinner than the P(VDF‐TrFE) nanofibers mat layer was used along with the switching polarity test confirmation, indicating that the energy harvesting signal came from the piezoelectricity of the device. [ 19,20,78 ] Figure S13 (Supporting Information) additionally shows the generated instantaneous power of energy harvesters depending on the different mechanical input forces and frequencies. The force and frequency‐dependent measurements were performed under the conditions of 1, 3, 5, 7, 10 N at the frequency of 1 Hz and 0.5, 1, 2, 4, 5 Hz at the applied force of 10 N, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, an encapsulation layer thinner than the P(VDF‐TrFE) nanofibers mat layer was used along with the switching polarity test confirmation, indicating that the energy harvesting signal came from the piezoelectricity of the device. [ 19,20,78 ] Figure S13 (Supporting Information) additionally shows the generated instantaneous power of energy harvesters depending on the different mechanical input forces and frequencies. The force and frequency‐dependent measurements were performed under the conditions of 1, 3, 5, 7, 10 N at the frequency of 1 Hz and 0.5, 1, 2, 4, 5 Hz at the applied force of 10 N, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF materials, which are ferroelectric and piezoelectric polymers with an electroactive β phase induced by a strong –CF 2 – dipole, [ 19,20 ] are reliably biocompatible, excellent processibility, and offer high chemical resistance with mechanical flexibility. [ 21,22 ] Ferroelectric materials such as PVDF have been introduced into several energy harvesting devices, and previous studies have shown that ferroelectric properties are also closely related to the performance improvement of triboelectric as well as piezoelectric energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…They deform in response to an applied voltage. This reverse piezoelectric effect is used in microactuators, ultrasonic generators, nanopositioning systems, acousto-optic modulators, active vibration damping, etc. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of inorganic materials is also manifested by high coupling coefficients, k , that represent the ratio of electrical to mechanical energy conversion . Some organic materials, and in particular fluorinated polymers, , also display piezoelectric properties. The most efficient ones include polyvinylidene fluoride (PVDF) and copolymers , such as poly­(vinylidenefluoride-trifluoroethylene) (PVDF-TrFE)), poly­(vinylidenefluoride-trifluoroethylene-chlorotrifluoroethylene) (PVDF-TrFE-CFE), or poly­(vinylidene fluoride-hexafluoropropylene (PVDF-HFP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are five kinds of polymorphic structures of PVDF in the form of α- and δ-(TGTG’), β-(TTT), γ, and ε-(T3GT3G′) (T for trans and G for gauche) [ 16 ]. In particular, PVDF with a high content of β-phase possesses excellent piezoelectric properties, which makes it a favorable material for piezoelectric nanogenerators (PENG) [ 17 ]. PVDF nanofiber-based nanogenerators have the potential to be manufactured into self-charged face masks, which can generate electrical charges by the motion of the human body, thus improving the electrostatic filtration efficiency [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%